(untitled) (Revista de Ciências Agroveterinárias, 2019)
This study aimed to evaluate the lower base temperature (Tb), thermal time and grapevine phenology and kiwi cultivars. Twigs 25-35-cm long for the following cultivars: grapevine, Chardonnay (CH), Isabel (IS), Niágara Branca (NB), Concord (CO) and Bordô (BO); and kiwi, Bruno (BR), Monty (MO), Elmwood (EL), MG06 (MG) and Yellow Queen (YQ) were collected in orchards in Veranópolis, RS State, on 06/03/2015. Intact twigs packed in black plastic film were subjected to 1,008 chilling hours (HC) at 0°C in incubators to overcome dormancy and then transferred to temperatures of 4, 6, 8, 10, and 12°C on single-node cuttings planted in phenolic foam. Over 150 d, budburst of the buds was evaluated in 2-3-d intervals in the green-tip stage. The resulted inverse data for number of days to budburst (1/days to budburst) was inserted into regression curves to estimate Tb for each genotype. Historical phonological series comprised of 10-years for the analyzed cultivars and meteorological data of the cultivation sites were used to determine thermal time (degree-days) for the fruit trees during the growing season. Temperate fruit species exhibited different Tb. Tb was lower for kiwi cultivars (BR=3,0°C; MO=3,3ºC; EL=3,1°C; MG=3,2°C and YQ=3°C) and higher for grapevine cultivars (CH=4,2°C; IS=4,3°C; NB=4,1°C; CO=6,2°C; and BO=4,4°C). The thermal time, in degree-days (DD), varied from 1670.9 to 2060.7 for grapevine cultivars and from 3179.6 to 3762.0 for kiwi cultivars. The higher DD sum for kiwi crop was given by the higher number of days of its vegetative cycle associated to lower Tb of the genotypes, when compared to the grapevine crop. The phenological subperiod (budburst to maturation) of the fruit trees in 100% of the assessed cases responded more to thermal time (degree-days) than to chronological time (d) to complete the vegetative cycle.